Reconceptualising the agenda for education in the Caribbean: Proceedings of the 2007 Biennial Cross-Campus Conference in Education, April 23-26, 2007, School of Education, UWI, St. Augustine, Trinidad and Tobago - Quamina-Aiyejina, Lynda (School of Education, UWI, St. Augustine, 2008)
This volume contains the proceedings of the 2007 Biennial Cross-Campus Conference of the Schools of Education of The University of the West Indies (UWI). The papers are organized under six headings: Part 1: Best Practices in Instruction; Part 2: Issues of Curriculum; Part 3: Educational Administration; Part 4: Education and National Development; Part 5: Measurement and Evaluation; and Part 6: Professional Development of Educators
Keywords: Educational reform; Conference proceedings; School of Education, UWI; Caribbean